Increasing Coal Crushing Production at PT. XYZ Using Lean Six Sigma Approach - Ahmad Fauzi; Suparno Suparno (Publikasi Indonesia, 2025)
Coal is a primary energy source in Indonesia, particularly for steam power plants (PLTU). The coal crushing process at PT. XYZ is a critical stage in coal mining operations; however, the company faces operational challenges that hinder the achievement of production targets. This study aims to identify the main issues, analyze factors affecting productivity, and design effective improvement solutions. The methodology used is DMAIC (Define, Measure, Analyze, Improve, Control). In the Define phase, process mapping and waste identification were conducted. The Measure phase utilized a Pareto diagram to determine key issues. Root cause analysis using the 5 Why's method was performed in the Analyze phase. In the Improve phase, solutions were designed through Future State Mapping, while in the Control phase a Kanban Board for monitoring. The results show that Year-to-Date coal crushing production as of October 2024 reached 9.9 million MT, or 94% of the 10.56 million MT target, representing a 139% increase compared to October 2023, which only reached 7.2 million MT.